2021
DOI: 10.1007/s11625-021-00918-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experiencing the role of imaginary future generations in decision-making: a case study of participatory deliberation in a Japanese town

Abstract: To ensure sustainability, overcoming intergenerational conflict is vital, and social systems supporting decision-making that takes into account the benefits to future generations is thus critically important. One promising approach in such social systems is introducing “imaginary future generations” who act as representatives for the benefits of future generation in actual, present-day decision-making situations. In this study, we explore the effects and implications of participants’ experiences as representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…In deliberations of future generations, Feature 1 (statement from the current state) and Features 2 and 3 coexisted in the same subject's speech. Saijo [6,7] and Hara et al [11] argued that subjects in the role of IFGs looked at things from a perspective that looked at both positions of present and future generations. This paper traced the path to the acquisition of this bird's eye view from the change of topics covered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In deliberations of future generations, Feature 1 (statement from the current state) and Features 2 and 3 coexisted in the same subject's speech. Saijo [6,7] and Hara et al [11] argued that subjects in the role of IFGs looked at things from a perspective that looked at both positions of present and future generations. This paper traced the path to the acquisition of this bird's eye view from the change of topics covered.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the subjects were thinking from the perspectives of both the current and the future generations simultaneously. Hara et al [11] proposed the concept of "viewpoint sharing" from this finding. A high degree of viewpoint sharing can activate futurability, which can pave the way for the consideration of future generations.…”
Section: Concept Of "Future Design" (Fd) and The Role Of Deliberationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been conducted on the generation of futurability and it has been found that one of the promising methods to overcome the shortsightedness and activate futurability is the introduction of "IFGs" who are tasked with representing future generations in decision-making or negotiations by adopting the perspective of future generations (Hara et al, 2019;Kamijo et al, 2017;Saijo, 2018). The effectiveness of introducing IFGs has been demonstrated increasingly through experiments, field experiments, questionnaire surveys, and actual practice (Hara et al, 2019(Hara et al, , 2021Kamijo et al, 2017;Nakagawa et al, 2019;Saijo, 2020). For example, the first practice session adopting IFGs, which was held in the town of Yahaba in Iwate Prefecture, Japan, demonstrated that the ideas and policies proposed by groups of IFGs were in stark contrast with those of current generations groups (Hara et al, 2019).…”
Section: Incorporating the Viewpoints Of Future Generationsmentioning
confidence: 99%
“…Furthermore, the introduction of IFGs has been so far conducted in a variety of policy fields, such as in the water environment, renewable energy, and urban planning (Hara et al, 2019(Hara et al, , 2021Kuroda et al, 2021;Nakagawa et al, 2019;Uwasu et al, 2020). Although the introduction of IFGs has been attempted in these studies with public policy-related themes, no studies have been conducted on identifying research agendas, development, and technological innovation using the case of academic research to date.…”
Section: Introductionmentioning
confidence: 99%